Effects of Fe, Mn, chemical grain refinement and cooling rate on the evolution of Fe intermetallics in a model 6082 Al-alloy - Amit Das (Intermetallics, 2021)
The solidification microstructures formed in a model 6082 alloy with 0.2–1.0 wt % Fe were examined under different cooling rates and the effects of 0.5 wt % Mn and Al–5Ti–1B grain refiner addition investigated. The results were compared against Thermo-Calc, differential scanning calorimetry (DSC) and cooling curve analysis. Fe promotes primary-Al grain refinement from growth restriction and constitutional undercooling effects but increases detrimental β–(Al9Fe2Si2) intermetallic. Mn contributes to primary-Al grain refinement from growth restriction and promotes the formation of α–Al15(Fe,Mn)3Si2 at the expense of increased intermetallic content. Al–5Ti–1B inoculation not only produces the strongest refinement of primary-Al grains but also refines the Fe-intermetallics by enhancing their nucleation and restricting their growth volume in the interdendritic liquid pockets.